Analisis Tingkat Kematangan Learning Management System SMAN 1 Parongpong Menggunakan Framework COBIT 5 Domain DSS03 & MEA01 - Mendrofa, Seprianto; Sihotang, Jay Idoan (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Information technology in an organization is very useful if it is used with good goals and according to the company's standard requirements. SMAN 1 Parongpong is one of the schools that has utilized information technology by using the Learning Management System learning system, namely with the existence of the SMANPAR E-Learning which started in 2019, but until now there has never been a measurement of the maturity of its system for learning. This study aims to determine the maturity level of the Learning Management System using COBIT 5.0 (Control Objectives for Information and Related Technologies), especially in the DSS (Decision, Support and System) and MEA (Monitor, Evaluate, and Assess) domains. The population in this study were students of SMAN 1 Parongpong with a total of 93 respondents, teachers with a total of 50 respondents, and the included IT party totaling 8 respondents. The data collection technique in this study is a quantitative method that will be used when analyzing the data collected through the results of questionnaires and making comparisons with guidelines from COBIT 5 between the DSS and MEA domains. The results of the research that has been done show that the use of information technology from SMANPAR E-Learning is at maturity level 4-Predictable, but it should be noted that the use of SMANPAR E-Learning is still not optimal in supporting the school's academic community with maturity level ideally 5-Optimizing with a Student/Student gap value of 1.25, Teachers of 1.25 and IT Staff of 0.44.